STUDIED ON DYNAMIC STRESS RESPONSE OF 20CrMnTi STEEL UNDER IMPACT LOAD AND CONSIDERED FOR ADIABATIC TEMPERATURE RISE MODIFICATION OF THE J-C CONSTITUTIVE MODEL - WANG JiaBin; DING Jun; SONG Kun; HUANG Xia; ZHANG XiaoDi; WANG LuSheng (Jixie qiangdu)
In this paper, the quasi-static tensile tests and the dynamic compression tests of 20 CrMnTi were carried out using the tensile tester and Split Hopkinson pressure bar（SHPB） device at different strain rate to study the dynamic stress response of 20 CrMnTi steel. The results show that 20 CrMnTi steel has strain rate effect and plasticizing effect. But it is not very sensitive to strain rate change within the scope of dynamic compression experiment. In consideration of the adiabatic temperature rise, the Johnson-Cook constitutive model is modified. The results show that the revised Johnson-Cook constitutive model can well describe the mechanical performance of 20 CrMnTi under the dynamic impact load, which is important to reference value that 20 CrMnTi steel is applied under high speed and overload.